Prawda jako narzędzie transgresji. Parezja a postawa nowoczesności w filozofii Michela Foucaulta - Kowalczyk, Michał (Hybris, 2019)
In the article I analyze the idea of the Enlightenment in Michel Foucault’s philosophy. Also, I analyze a few possible practices of parrhesia which Foucault has been studying during his career. I try to show up the connections that in my opinion exist between these two issues. I describe the idea of ethos of modernity as the „methodological frame”, which can be analyzed as a kind of „clue” for the subjective action in modernity. Parrhesia, then, can be a specific action that we can practice as the ethos of modernity.